Extreme Value Distributions in Hydrological Analysis in the Mekong Delta: A Case Study in Ca Mau and An Giang Provinces, Vietnam - Kien Cuong, Dang; Ton Dam, Duong; Ton Thai Duong, Duong; Kim Loi, Nguyen; Vo, Nguyen-Son; Kortun, Ayse (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2019)
Climate change poses a critical risk to the sustainable development of many regions in Vietnam, especially in the Mekong River. In this paper, we show the specific extreme value distributions of rainfall, flow, and crest of salinity based on the hydrological data from 1975 to 2017 in An Giang and Ca Mau provinces in the Mekong Delta. We also derive a theoretical model and validate its accuracy compared to the empirical data over the years. The results demonstrate that the extremely high flows increase in both magnitude and frequency, while the extremely low ones are projected to occur less often under the climate change. The results can further help the local governments reduce the risk of lack water in dry season, control the salinization, and avoid the threat of flooding in the downstream of the Mekong Delta.
Keywords: Extreme value distribution; Gumbel distribution; max-domain of attraction; maximum likelihood estimation; Newton – Raphson method; Mekong Delta